1973
DOI: 10.1063/1.1679448
|View full text |Cite
|
Sign up to set email alerts
|

Accurate ab initio calculation of the BeH molecule. I. The X 2Σ+ and A 2Π states

Abstract: Results of calculations using a configuration interaction LCAO-MO method are presented for the X 2Σ+ and A 2Π states of BeH. Apart from the 1s shell of Be, the correlation energy of the remaining three electrons is calculated quantitatively using an extended basis set and complete configuration interaction including all single, double and triple replacements. The calculated spectroscopic constants are in excellent agreement with available experimental data. The present calculations also predict a value of De(B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

1975
1975
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 22 publications
3
27
1
Order By: Relevance
“…After considerable experimentation, it was found that an optimum combined-isotopologue direct potential fit to the global data set, with the vibration-rotation levels of the A 2 P and C 2 R + states being represented by independent term values, was provided by an EMO 3 (5,9) potential function for the X 2 R + state. Since Be has only one stable isotope, only theS H ad ðrÞ potential-energy BOB function can be determined, and as mentioned above, its asymptotic value is fixed at u H 1 ¼ 0:0 [21].…”
Section: Direct-potential-fit (Dpf) Analysis Of the Ground X 2 R + Statementioning
confidence: 99%
See 1 more Smart Citation
“…After considerable experimentation, it was found that an optimum combined-isotopologue direct potential fit to the global data set, with the vibration-rotation levels of the A 2 P and C 2 R + states being represented by independent term values, was provided by an EMO 3 (5,9) potential function for the X 2 R + state. Since Be has only one stable isotope, only theS H ad ðrÞ potential-energy BOB function can be determined, and as mentioned above, its asymptotic value is fixed at u H 1 ¼ 0:0 [21].…”
Section: Direct-potential-fit (Dpf) Analysis Of the Ground X 2 R + Statementioning
confidence: 99%
“…With only five electrons, the beryllium monohydride molecule has been the target of many ab initio calculations [9][10][11][12][13][14][15][16][17][18], and is often used to test new methods for open-shell systems. The availability of information for three isotopologues and its small reduced mass also make beryllium monohydride an interesting species for examining BornOppenheimer breakdown (BOB) effects.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we follow the notation of Colin and De Greef. 36 The two valence states labeled as C 2 ⌺ + and A 2 ⌸ have been extensively studied 26,28,39,45,49,50,52,54,[105][106][107] and their respective emission bands were reported several years ago. 37,[111][112][113][114] The experimental parameters of the C 2 ⌺ + state correspond to those calculated for the 2 2 ⌺ + state because all the avoided crossings in which the C 2 ⌺ + state is involved occur in the repulsive branch and above the dissociation limit of the state, so that the bound vibrational-rotational levels are not perturbed and the spectroscopical study, at the approached level of the present work, is not complicated by other electronic states.…”
Section: Spectroscopic Parametersmentioning
confidence: 99%
“…Several works that have dealt with the low-lying states of BeH describe the important mixings in either the 2 ⌸ or the 2 ⌺ + states. 26,41,[47][48][49][50][51][52][53][54][55][56][57][58][59] BeH offer other properties that make it a good choice for a comprehensive FCI study. Apart from the above mentioned avoided crossings, we can mention its open-shell nature, the possible occurrence of featured potential wells at large R values ͑e.g., the controversial double-well nature related to the so-called G 2 ⌸ state or the properties associated to the existence of a second minimum in the potential curve of the B 2 ⌸ state 52 ͒, the problem of the position of the ͑4s͒ 2 ⌺ + state ͑theoretically predicted 47,53 as lying at higher energy than the ͑3d͒D state, which does not agree with reported experimental values 36 ͒, not to mention the rather uncommon fact of a single chemical bond dissociating into a neutral closed-shell atom of just four electrons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation